Telehealth and people with disabilities in the United Kingdom: a scoping review - Mezhen Ko; Mezhen Ko; Matthew Azzopardi; Constantinos Loizou; Abison Logeswaran; Benjamin Ng; Agata Pacho; Yu Jeat Chong (Frontiers in Public Health)
IntroductionTelehealth, also sometimes known as telemedicine, is the use of communication technologies to deliver healthcare remotely, has become increasingly vital, particularly since the COVID-19 pandemic. While telehealth can improve healthcare access, it may exacerbate inequities for people with disabilities. This scoping review explores the needs, experiences, and difficulties people with disabilities face when accessing telehealth services in the United Kingdom’s (UK) National Health Service (NHS).MethodsA systematic search was conducted using the PRISMA for Scoping Reviews (PRISMA-ScR) guidelines. The search terms included variations of “telehealth,” “disability,” “impairment,” “United Kingdom,” and “NHS.” Studies published after January 2010 were included if they addressed the experiences of people with disabilities when using telehealth. Ten studies met the inclusion criteria, and findings were synthesized into five key themes: patient and carer satisfaction, benefits of telehealth, healthcare provider perspectives, disability-specific barriers, and technological barriers.ResultsThe studies highlighted varied experiences across different disabilities, telehealth technologies, and medical specialties. While patients and carers generally expressed satisfaction with telehealth’s convenience and accessibility, a preference for face-to-face consultations remained. Key barriers included technological challenges such as poor internet connectivity, unfamiliarity with digital tools, and device access, as well as disability-specific challenges, particularly for sensory impairments. Reported benefits of telehealth included improved access to care and flexibility for patients with disabilities. However, healthcare provider perspectives highlighted concerns about the ability to build a rapport and perform thorough assessments remotely.ConclusionTelehealth should complement traditional care through a hybrid approach. Future efforts must focus on improving technological accessibility, training healthcare providers, and co-designing solutions with patients to promote equitable healthcare access for people with disabilities.